Conflict analysis in chemical wastewater management: A case study on the recycling process in the heavy equipment industry in Jakarta - Aristya Wahyu Murdiana (Environment Conflict, 2024)
Background: One cause of water degradation is the large quantities of water consumption in industries, along with water pollution. Recycling wastewater offers a solution to this problem. As a wastewater-producing company, XYZ has implemented this solution. However, analysis of wastewater management revealed that some WWTPs did not meet the clean water requirements, necessitating additional processing units, specifically the addition of a recycling unit. Method: The recycling unit was added to reduce wastewater chemicals such as arsenic, iron, fluoride, cadmium, and others. A comparative analysis was conducted to assess the effectiveness of the recycling unit. Findings: The comparison indicated that the water parameters of the recycling unit’s effluent results were better than PDAM parameters, showing improvements in the water chemistry. Conclusion: The effectiveness of the recycling unit was validated, as it significantly lowered some chemical parameters in wastewater, producing effluent that was better than PDAM water and meeting the clean water quality standards outlined in Permenkes No. 416 of 1990 on Water Quality Monitoring. Novelty/Originality of this article: The novelty of this article lies in demonstrating the effectiveness of an added recycling unit in improving wastewater quality. It highlights a successful case of reducing harmful chemicals to surpass PDAM water quality, adhering to national standards.